2007
DOI: 10.1111/j.1475-2743.2007.00084.x
|View full text |Cite
|
Sign up to set email alerts
|

Walkley–Black analysis of forest soil organic carbon: recovery, limitations and uncertainty

Abstract: Organic carbon levels of 542 soil samples from temperate lowland forest were determined by the original and modified Walkley–Black (WB) dichromate methods and total organic carbon (TOC) analysis. The performance and the lower and upper quantification limits of the WB method were assessed. Variable recovery rates were related to laboratory and field conditions and to the sample composition. The percentage carbon recovered by the original WB method was found to be systematically lower than commonly accepted, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(83 citation statements)
references
References 19 publications
3
79
0
1
Order By: Relevance
“…Soil samples taken at the center of each plot allow for the determination of soil organic carbon (SOC), which is still ongoing. For AAB, preliminary SOC was estimated using a modified Walkley-Black method [113][114][115] from samples sent to the Laboratoire des Radio Isotopies (LRI) in Antananarivo, Madagascar. Estimates of carbon calculated based on plot measurements in all AOIs were scaled to the ha-level.…”
Section: Application Of Mapping Resultsmentioning
confidence: 99%
“…Soil samples taken at the center of each plot allow for the determination of soil organic carbon (SOC), which is still ongoing. For AAB, preliminary SOC was estimated using a modified Walkley-Black method [113][114][115] from samples sent to the Laboratoire des Radio Isotopies (LRI) in Antananarivo, Madagascar. Estimates of carbon calculated based on plot measurements in all AOIs were scaled to the ha-level.…”
Section: Application Of Mapping Resultsmentioning
confidence: 99%
“…The correction factor of 1.58 proposed by De Vos et al (2007) was used to convert the Aardewerk carbon concentration into total organic carbon. De Vos' correction factor compensates for the incomplete oxidation of Walkley and Black's carbon extraction method.…”
Section: Reference Year 1960mentioning
confidence: 99%
“…Lettens et al (2005a) ). These differences may be explained by the following reasons: (1) We used data from a revised/ corrected version of the Aardewerk database (Legrain 2005), (2) we considered MSU/RFIW associations and not landscape units for spatial generalization, so the forest reference area is not exactly the same, and (3) we used a correction factor of 1.58 (De Vos et al 2007) instead of 1.32 (Walkley and Black 1934) to compensate for the Sources of error and accuracy of the estimates Imprecision may occur at different levels (field sampling, measurement method, work assumptions, and simplifications) and be related to different phases of the estimation procedure (especially when mixing data from several sources). Goidts et al (2009) showed that sources of uncertainty linked to the soil CS of Wallonia's land under agriculture increased with the sampling scale.…”
Section: Littermentioning
confidence: 99%
See 1 more Smart Citation
“…In western Micronesia, specifically Yap state and the Republic of Palau, mangrove C storage ranged from 479 (seaward) to 1385 (landward) Mg/ha, with 70% of storage in soils [27]. While the C stocks reported here are not nearly as high as those reported in the Indo-Pacific and western Micronesia, Madagascar's mangroves are typically of a lower stature, and our soil samples were only collected to 1.5 m. In addition, our soil samples were analyzed using the Walkley-Black method, which is known to under-represent SOC [114][115][116][117][118]. However, as there are few professional laboratories in Madagascar that analyze soil, and all employ only this approach, we chose the LRI, given the expense of sending samples abroad to be analyzed and the critical need to build local scientific capacity.…”
Section: Carbon Stocks Of Mapped Mangrove Classesmentioning
confidence: 99%